Pengaruh Kompetensi, Disiplin, dan Stress Kerja Terhadap Kinerja Karyawan pada PT Vayata Senada Cemerlang - Olivia Olivia; Seanny Augie; Caroline Caroline; Cut Fitri Rostina (Journal of Economic, Bussines and Accounting (COSTING), 2022)
PT Vayata Senada Cemerlang is a company engaged in the sale of building material distributors. So that in the company there are various employee problems such as decreased performance. Employee performance decreased due to several factors, namely competence, discipline and employee work stress. This research will be conducted with a quantitative approach that is descriptive explanatory. Methods of data collection can be done with a questionnaire. The method used is multiple regression. The results of this study indicate that the results of the calculation of the partial hypothesis testing obtained the value of tcount |2,612| > ttable |2.04|and significant 0.014 <0.05. Discipline variable obtained tcount |3,000| > ttable |2.04| and significant at 0.005 < 0.05. The work stress variable obtained the value of tcount |-3,169|> ttable |-2,04| and a significant value of 0.003 <0.05. Test results Fcount |14,790| > Ftable |2.91| and significance probability 0.000 < 0.05. The conclusion in this study is the influence of competence, discipline and work stress partially and simultaneously has a positive and significant effect on employee performance at PT Vayata Senada Cemerlang. Keywords : Competence, Discipline, Work Stress, Performance